Social and Economic Factors Affecting the Incidence of Anemia in Pregnant Women - Erna Eka Wijayanti; Yudhi Anggoro; Nurul Hidayati; Munawarah Munawarah (PT. Anagata Sembagi Education, 2024)
Anemia in pregnant women is a significant health problem, with adverse effects on the health of the mother and baby. This study aims to identify social and economic factors that affect the incidence of anemia in pregnant women in certain regions. Quantitative approach with cross-sectional design was used to collect data through questionnaires and structured interviews on 200 pregnant women. Factors analyzed include education, family income, type of employment, access to health services, and diet. The results showed that low levels of education, low family income, and limited access to health services were significantly associated with an increased risk of anemia in pregnant women. In addition, social support factors also play an important role in preventing anemia. These findings suggest that social and economic factors interact, with lower education associated with lower incomes, which in turn hinders pregnant women's access to good nutrition and adequate health care. Based on the results of the study, it is suggested that the health policy of pregnant women more emphasis on nutrition education, increased access to health services, and economic empowerment, especially among low-income families. This study provides an important contribution in formulating intervention programs that can reduce the prevalence of anemia in pregnant women in Indonesia.